Roles of inflammasomes in viral myocarditis - Xu, Jingyu; Zhou, Zihao; Zheng, Yidan; Yang, Sai; Huang, Kun; Li, Huili (Frontiers in Cellular and Infection Microbiology, 2023)
Viral myocarditis (VMC), characterized by viral infection induced inflammation, is a life-threatening disease associated with dilated cardiomyopathy or heart failure. Innate immunity plays a crucial role in the progression of inflammation, in which inflammasome is providing a platform for the secretion of cytokines and mediating pyroptosis. Inflammasome is a rising star gaining increasing attention. The nucleotide oligomerization domain-, leucine-rich repeat-, and pyrin domain-containing protein 3 (NLRP3) inflammasome and caspase recruitment domain-containing protein 8 (CARD8) inflammasome are two inflammasomes which were reported affecting the process and prognosis of VMC. These two inflammasomes, which consists of several components, can be activated by a wide range of cellular events. Accumulating evidence has suggested that inflammasomes are involved in different stages of VMC, including the trigger and progression of inflammation in cardiomyocyte, and myocardial injury or myocardial remodeling after infection. In this review, we summarized the mechanisms and pathways of inflammasomes in VMC and discussed the potential therapeutic strategies targeting the inflammasomes and the related pathways.